PENGARUH PEMBERIAN EKSTRAK DAUN GAMAL (Gliricidia sepium) DENGAN INTERVAL PENYEMPROTAN TERHADAP PERTUMBUHAN BIBIT KOPI ARABIKA (Coffea arabica L.) Varietas Ateng super - Mulyono, Mulyono; Rosalina, Olyfia; Arjuna, Windi (Cangkok, 2021)
Arabica coffee (Coffea arabica L.) is a traditional type of coffee with the best taste. Most of the coffee available is made using Arabica coffee beans. This coffee comes from Ethiopia and is now cultivated in various parts of the world, from Latin America, Central Africa, East Africa, India, and Indonesia. The coffee plant is thought to have come from the Adeh Ababa mountains on the African continent, precisely in the country of Ethiopia in the 9th century, a person named Kaldi accidentally ate raw coffee beans obtained from shrubs, he felt extraordinary changes after eating the coffee beans, then he told this to local residents and then spread to various areas (Panggabean, 2011). According to the Association of Indonesian Coffee Exporters and Industry (AEKI), the average volume of Indonesian coffee exports is around 350,000 tons per year, covering 85 percent of Arabica and 15 percent of Robusta. With more than 50 export destination countries including the USA, Japan, Germany, Italy, and Malaysia being the main destinations (Anonymous, 2016). To obtain purity of seed quality, seeds should be obtained directly from captive breeding/trusted seed distributors. Coffee seeds must come from certain desired clones, seeds that are attacked by powdery pests and abnormal ones are not used (Najiyati and Danarti, 2000).